2017
DOI: 10.18632/oncotarget.18260
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the tumor-promoting microenvironment in MET-amplified NSCLC cells with a novel inhibitor of pro-HGF activation

Abstract: Targeted therapeutic agents, such as inhibitors of epithelial growth factor receptor (EGFR), have transformed the management of non-small cell lung cancer (NSCLC) patients. MET-amplified NSCLC cells display resistance to EGFR-targeting agents, but are addicted to MET signaling for survival and proliferation and are sensitive to MET inhibition. However, responsive cancer cells invariably develop resistance to MET-targeted treatment.The tumor microenvironment plays a major role in resistance to anticancer therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 63 publications
2
28
0
Order By: Relevance
“…HGF or pro-HGF-producing fibroblasts inhibit not only the response to individual treatment with a MET kinase inhibitor, but also the response to dual inhibition of EGFR and MET [119]. We demonstrated that HGF reactivates MET, EGFR and RON signaling and restores AKT, ERK and WNK1 activation in MET-inhibited cells.…”
Section: Hgf/met Signaling Is a Hallmark Of Therapeutic Resistancementioning
confidence: 82%
“…HGF or pro-HGF-producing fibroblasts inhibit not only the response to individual treatment with a MET kinase inhibitor, but also the response to dual inhibition of EGFR and MET [119]. We demonstrated that HGF reactivates MET, EGFR and RON signaling and restores AKT, ERK and WNK1 activation in MET-inhibited cells.…”
Section: Hgf/met Signaling Is a Hallmark Of Therapeutic Resistancementioning
confidence: 82%
“…Moreover, structural analysis of the complexes of KD1 and HGF/SF‐activating proteases may have significant implications for the development of synthetic chemicals that specifically inhibit proteolytic activation of HGF/SF and MSP. To date, several promising small molecular weight compounds that specifically inhibit the HGF/SF‐activating proteases have been reported . Generation of neutralizing antibodies against these proteases may also be a useful approach.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Amplification of MET in lung cancer is a well-known mechanism of resistance to epidermal growth factor receptor-targeted tyrosine kinase inhibitors (EGFR-TKIs) [105][106][107]. In addition, overexpression of HGF is observed in approximately 61% of patients with EGFR-TKIs-resistant lung cancer and is known as a cause of acquired resistance [106,107].…”
Section: Discussionmentioning
confidence: 99%
“…HGF/MET signaling-induced EMT is a major phenomenon in various cancer cells [104]. Recently, it has been reported that HGF/MET signaling-induced inhibition of SMURF2 yielded stabilization of TGF-β receptor, and that upregulation of TGF-β signaling axis leads to EMT of UC cell line [105]. However, compared with PC and RCC, the function of TTSPs and HAIs in UC is not well known.…”
Section: Significance Of Hgf-dependent Met Activation In Muscle Invasmentioning
confidence: 99%